Remittances and portfolio values: An inquiry using Spanish immigrants from Africa, Europe and the Americas - Catalina Amuedo-Dorantes; Susan Pozo (Institute for the Study of Labor (IZA), 2012)
Using a recent Spanish database, we show that remittances respond to cross country differences in portfolio values. This behavior suggests that immigrants are sophisticated economic optimizers who take advantage of opportunities to invest trans-nationally given the networks that immigrants are likely to have developed both in their host and home communities. The responsiveness to portfolio variables persists whether immigrants are highly or less highly educated. However, there are differences in the individual portfolio variables to which immigrants from various regions of the world respond to, as we would expect given migrants' diverse backgrounds and motives for emigrating. Additionally, remitting patterns change over time with the length of the migration spell, suggesting that remittances sent for portfolio motives become more likely as the immediate needs of family left back home are addressed and immigrants settle down in their host communities.
Keywords: F24; F22; 330; remittances; portfolio motives; Spain; Rücküberweisung (Migranten); Haushaltseinkommen; Portfolio-Management; Migranten; Schätzung; Spanien